2010
DOI: 10.7763/ijtef.2010.v1.30
|View full text |Cite
|
Sign up to set email alerts
|

The Satisfaction Level of Penang Private Colleges Lecturers

Abstract: Abstract-Porter's generic strategies remain one of the most widely accepted typology of strategic options for businesses. Using a survey a sample of 69 hotel managers from the Nord-West part of Romania was questioned about their current strategic practices. A factor analysis revealed that hotels are pursuing only two strategies that can be identified as those of Porter. The regression analysis was used in order to test if there are certain practices that correlate with the strategies identified earlier in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In fact, employees' job satisfaction is significantly related to recognitions like pay raise and promotion (Ali &Ahmed, 2009). Ch'ng, Chong, andNakesvari (2010) found that the job satisfaction of lecturers in Malaysia is related to salary and promotion opportunities. Since the appraisal and promotions system at local HEIs are based on KPIs (Azizan et al, 2012), the university staff can strategically align their goals toward achieving the institution's targets.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, employees' job satisfaction is significantly related to recognitions like pay raise and promotion (Ali &Ahmed, 2009). Ch'ng, Chong, andNakesvari (2010) found that the job satisfaction of lecturers in Malaysia is related to salary and promotion opportunities. Since the appraisal and promotions system at local HEIs are based on KPIs (Azizan et al, 2012), the university staff can strategically align their goals toward achieving the institution's targets.…”
Section: Discussionmentioning
confidence: 99%
“…This research revealed that benefit is a critical factor in job satisfaction. Furthermore, another study showed benefits have a significant positive relationship with employees' job satisfaction in a private college (Ch'ng et al, 2010).…”
Section: Resultsmentioning
confidence: 97%
“…Some factors which may directly influence HRQoL are salary, total experience, promotion opportunities, academic position or job rank, students' and colleagues' attitude, and working environment [4][5][6]. Several other demographic factors such as age, gender, race, level of education, and working hours are also associated with the quality of life of university academics [7].…”
Section: Introductionmentioning
confidence: 99%